2015
DOI: 10.11144/javeriana.ie18-1.cefc
|View full text |Cite
|
Sign up to set email alerts
|

La calidez en enfermería: formulación de constructo y variables relacionadas

Abstract: <p>La calidez es un fenómeno subjetivo fundamental en las relaciones personales. La calidez se contagia y, así, puede ser un factor favorecedor en el cuidado, mas no existe consenso en su definición ni dominios. Medir la calidez es significativo, pues es un predictor de satisfacción usuaria; sin embargo, no se encontraron modos de medirla, lo que motivó esta revisión. <em>Objetivos:</em> Identificar en la revisión teórica comportamientos<br />que representen la calidez del enfermero y o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…demonstrated that competence and respect may depend more on perceived competence; whereas, liking and fondness are associated with perceived warmth. Human warmth may influence social judgments in people in so many ways, but also admiration may depend heavily on perceived competence and patient satisfaction (Lagos Sánchez et al, 2016;Wojciszke, Abele, & Baryla, 2009).…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that competence and respect may depend more on perceived competence; whereas, liking and fondness are associated with perceived warmth. Human warmth may influence social judgments in people in so many ways, but also admiration may depend heavily on perceived competence and patient satisfaction (Lagos Sánchez et al, 2016;Wojciszke, Abele, & Baryla, 2009).…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Instead, some medical facilities emphasize medical technology services rather than the patient's care(Capozza, Boccato, Andrighetto, & Falvo, 2009). Recent studies show that human attributes like honesty and likeability linked to warmth-related Revista de Psicología de la Salud (New Age) Vol 8, nº1, 2020 101 traits in people.However, LagosSánchez et al (2016), argue that it is necessary to examine characteristics of warmth in the nursing staff and services.It can provide some insight, and it may be a relevant factor that describes a patient's satisfaction. It becomes even more critical in the health area, and that nursing professionals have substantialparticipation in the health workforce in Puerto Rico.…”
mentioning
confidence: 99%
“…23,28 Team attitudes contribute to the varying sense of dignity of these patients, and teams with greater knowledge of the later stages of life are able to provide greater comfort to these individuals. 7.23 Behaviors such as eye contact, smiling, empathy and sensitivity to patient values, as well as maintaining privacy, are actions that contribute to patient satisfaction, as well as to greater bonding and trust, 7,19,29 fundamental characteristics for patient care, with a positive impact on their sense of dignity. The absence of these factors contributes to a decreased sense of dignity.…”
Section: /15mentioning
confidence: 99%